STRATEGI DAN SKENARIO PERENCANAAN KOTA CHICAGO, ILLINOIS, AS - Sitti Sarifa Kartika Kinasih (Jurnal Tekno Global, 2018)
The research about urban design within sustainable development system in Chicago descripts about environmental planning, renewable energy, to be appropriated with economic development that is going on in the city. Sustainability planning in the first skyscraper city in the world began with Heat Wave tragedy that caused by the global warming effect on 1995 having 3 eminent programmes, include Chicago Climate Action Plan, Chicago Green Roof Program, and Chicago Conservation Corps. The earnestly of this city on sustainable development showed from the unceasing and effectively city strategies and ordinances that launched by the Chicago government, also the departments is very massive to support sustainable development. Fund incentive, technical support, and great enthusiasm is totally given to the Chicago inhabitants. The research method that used to explain this research is content analysis. The environment responsibility showed on Chicago city  government’s care for the aspect of waste, water, green roof, land, and tenant aggrement. The economic opportunities showed on Chicago city  government’s care for the aspect of transportation, air, and energy. The social equity principal showed by Chicago city  government’s actions with made a rehabilitations for slum areas, make research about housing and job opportunities, made a coalition for comprehensive education fund intercities, and made a Chicago conservation corps.Keywords: sustainable development, city, environment, resource, policy